No Circles, Bill! (Cimarron Legend, 1992)
Clipping reads : No, circles, Bill! Go with the Grain!!! Cimarron's volunteer firefighters spent Saturday sprucing up their house, and Monday evening burning down somebody else's. (See Story, back page.)
Newspaper clipping with photograph of volunteer firefighter
Mater List Item # 10
File location is in the New Mexico File Cabinets
Keywords: Volunteer firefighters -- Cimarron; Painting Photographs; House Repair; Cimarron, New Mexico